KINERJA FASILITAS KOMERSIAL STASIUN KERETA API : PERSEPSI VS HARAPAN - Syahriyah, Dewi Rachmaniatus; Asriana, Nova (Jurnal Arsitektur ARCADE, 2021)
Abstract: The operation of railway station facilities prioritizes comfort, security and safety. In addition, the station also has high commercial value with commercial facilities. The role of users in commercial facilities as visitors to commercial facilities is very important. This relates to the level of comfort and satisfaction felt by visitors. This research will discuss about the performance of commercial facilities in order to get a railway station commercial facility arrangement that can adjust the level of comfort and user satisfaction. The level of comfort is indicated by the value of the visitor's perception, while the level of satisfaction is indicated by the value of visitor expectations of the railway station commercial facilities. Quantitative analysis was performed using the quadrant analysis method. The selected case studies are Bandung Station and Kiaracondong Station. The results of the analysis show that there are two important elements in the arrangement of commercial facilities for the railway station, namely disability facilities and family facilities. The results of this analysis are expected to be the basis for the planning of the railway station commercial facilities.Abstrak: Penyelenggaraan sarana transportasi kereta api sangat memprioritaskan kenyamanan, keamanan dan keselamatan operasional. Selain dari sisi pelayanan transportasi, stasiun juga memiliki nilai komersial yang tinggi dengan adanya fasilitas komersial. Peran pengguna fasilitas komersial yaitu pengunjung fasilitas komersial sangatlah penting. Hal ini berkaitan dengan tingkat kenyamanan dan kepuasan yang dirasakan oleh pengguna fasilitas komersial. Pada penelitian ini akan membahas mengenai tingkat kinerja fasilitas komersial stasiun kereta api guna mendapatkan penataan fasilitas komersial stasiun kereta api yang dapat memenuhi tingkat kenyamanan dan kepuasan pengguna. Tingkat kenyamanan ditunjukkan dengan nilai persepsi pengunjung, sedangkan tingkat kepentingan ditunjukkan mencari nilai harapan pengunjung terhadap fasilitas komersial stasiun kereta api. Analisis dilakukan secara kuantitatif dengan metode analisis kuadran important performance analysis. Studi kasus yang dipilih adalah Stasiun Bandung dan Stasiun Kiaracondong. Hasil analisis menunjukkan bahwa terdapat dua elemen penting dalam penataan ini, yaitu fasilitas disabilitas dan fasilitas ibu dan anak. Â Hasil analisis ini diharapkan dapat menjadi dasar dalam rencana penataan fasilitas komersial stasiun kereta api.